O'Reilly TensorFlow World 2019, Santa Clara, CA. (O'Reilly Media, 2019)
"Open source TensorFlow 2.0 is driving the machine learning (ML) revolution around the globe. The TensorFlow World Conference Santa Clara 2019--the first international conference devoted to TensorFlow--provided the thousands who attended the conference with an extraordinary opportunity to see TensorFlow 2.0 in action, discover new ways to use it, and learn how to successfully implement it in their own enterprises. This video compilation offers you the chance to experience the TensorFlow World Conference yourself. If you get it and explore it, you'll come away with a firm understanding of the entire machine learning stack, TensorFlow 2.0, and the reasons why companies like Spotify, LinkedIn, Amazon, Twitter, and Uber use TensorFlow to solve complex business problems."--Resource description page